Trends dynamics in Psychiatric Systems today - Ramiro Verissimo (2011)
FThe author makes some epistemologicalconsiderations on the urge to spreadpsychosomatics. To begin with, the heavyburden of mental disturbs in health caresystems today lead to an absolute need fora proper psychosomatic training of generalpractitioners.Then the 50 years of increasingpsycopharmacological treatments availableaccount for the mainstream split-care model;as the number of psychiatrists who focuson logotherapy decreased systematicallywhile the professional body of nonmedicaltherapists has grown. Hence the impendingneed of psychosomatics as a counterbalanceto adequately deal with the bio-psychosocialaspects involved both in heath and indisease.Finally concluding that, between physicalismand panpsychism, Psychosomatic Medicinehas to find its way by getting rid of theoutdated cartesian dualism.